Single Phase PV Grid-Connected in Smart Household Energy System with Anticipation on Fault Conditions - Feri Yusivar; Rian Suryadiningrat; Aries Subiantoro; Ridwan Gunawan (International Journal of Power Electronics and Drive Systems (IJPEDS), 2014)
This paper proposes an algorithm of Smart household energy systems to anticipate fault conditions in power system grid. Single phase PV grid-connected in smart household energy system is a smart system that determines electrical supply conditions to the load in residential electrical system. The smart system is consisted of two voltage source, conventional electricity system from national electricity provider as preferred source and photovoltaic as the alternative source. In smart system, fault conditions can be anticipated by selecting the appropriate voltage sources to supply the load. The condition of smart system can be described in power flow regulation to the load by detection and identification of amplitude, phase angle, and frequency of the voltage source compared to the system reference. The system mechanism is based on detection of voltage source using static transfer switch (STS) with phase locked loop (PLL) as voltage detection algorithm which output is used to determine decision logic algorithm for switching conditions. The results show that conditions of smart power system flow can be obtained based on voltage source selection in decision logic when fault condition occurs.DOI: http://dx.doi.org/10.11591/ijpeds.v4i1.5368